Logosfera a etyka społeczeństwa komunikacji - Lepa, bp Adam (Annales. Etyka w Życiu Gospodarczym, 2008)
This paper is concerned with the attitude of communication society towards the layer of ethicalvalues. Contrary to what constitutes information society, the conception of communication society isbased on the credibility of information, which is a significant component of human communication,and social bonds, which are the basis for any communication.Therefore, it is hypothesized that logosphere, which is the environment of the word, caneffectively influence the ethical foundations of communication society and contribute tothe development of such society. The chief asset of logosphere is based on its properties: the primacyof the word, dialogicity, and its environmental character. Owing to these features logosphere canpositively affect the ethical layer of communication society, provided it constitutes an arrangedenvironment of the word.